Postnatal consultation: Reports of obstetric violence (Research, Society and Development, 2022)
Objective: to describe how the nurse can identify, in the puerperal consultation, women who have suffered obstetric violence in the maternity ward. Methodology: this is an integrative literature review, in which the Virtual Health Library (VHL) was used as a database for the collection of articles, the studies of the last 05 years were analyzed, available in full and in the Portuguese language. Result: when analyzing the crossing between the descriptors “Obstetric violence” AND “Postnatal care” in the VHL, 14 results were obtained in total. After selecting Portuguese-language articles published in the last 5 years (n= 6 results). After reading the title (n=02 articles). After reading the abstract (n=01 article). When the descriptors “Obstetric violence” AND “Complications of labor” were confronted, 05 articles were shown as a result, of which 02 were in Portuguese and published in the last 5 years. In sequence, with reading of titles and abstracts (n= 02 articles); so the total of studies evaluated were 03 articles. Conclusion: Therefore, through the present study, it was observed that women still suffer OV during their passage through the maternity hospital, in their prepartum, delivery and postpartum processes. Such violence violates their rights as a human being and is practiced by birth care professionals, in places that should take and offer more protection to these women. Unfortunately, these women end up having a negative childbirth experience.